Manajemen Air Bersih di Daerah Perdesaan: : Sudi Kasusa di Desa Saojo Kecamatan Pamona Utara, Kabupaten Poso - Fredrik Bastian Kawani; Olvit Olniwati Kayupa; Feliks Arfid Guampe; Vonny Ivanka Wiondy (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This study aims to address the challenges of clean water management in the rural village of Saojo, located in North Pamona, Poso Regency, Central Sulawesi, Indonesia. The research explores the critical issues affecting the village’s water supply, including undetected leaks in the distribution system, the limited availability of water sources, and the impact of prolonged droughts. The study employs a qualitative approach, allowing for an in-depth understanding of the socio-cultural and economic context influencing water management in the village. Data collection was conducted through semi-structured interviews with local government officials and water management personnel, as well as observations of the water infrastructure and community practices. The analysis was carried out using thematic analysis, where data from interviews and observations were transcribed, categorized, and linked to the research objectives. The findings reveal that poor infrastructure maintenance, a lack of modern technology for detecting leaks, and insufficient community involvement in water management are the main obstacles to ensuring a sustainable water supply. The research also identifies potential solutions, such as the installation of a Municipal Water Supply System (PAM), the exploration of new water sources in collaboration with the Pamsimas program, and investments in advanced leak detection technology. The study concludes that a comprehensive approach involving regular monitoring and maintenance, infrastructure upgrades, community engagement, and government-private sector collaboration is essential for improving the water supply system in Saojo. By addressing these challenges holistically, the village can achieve a sustainable and reliable clean water supply, thereby improving the quality of life for its residents.